2012
DOI: 10.1111/ceo.12017
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of perioperative antiplatelet and anticoagulant therapy for vitreoretinal surgery

Abstract: There were no cases of uncontrolled intraoperative haemorrhage or serious postoperative choroidal haemorrhage. Mild haemorrhagic oozing during vitrectomy and dispersed vitreous cavity haemorrhage postoperatively were common. For the majority of patients taking antiplatelet or anticoagulant medication, these agents can be safely continued in the vitreoretinal surgical perioperative period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
22
1
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 17 publications
1
22
1
1
Order By: Relevance
“…In a recent prospective study in 2013, Ryan et al 16 assessed the risk of bleeding during VR surgery in patients on anticoagulant and antiplatelet therapy. They found the perioperative bleeding risks in these patients were relatively low and concluded that anticoagulants and antiplatelet agents may be safely continued for the majority of patients undergoing VR surgery.…”
Section: Other Ocular Surgerymentioning
confidence: 99%
“…In a recent prospective study in 2013, Ryan et al 16 assessed the risk of bleeding during VR surgery in patients on anticoagulant and antiplatelet therapy. They found the perioperative bleeding risks in these patients were relatively low and concluded that anticoagulants and antiplatelet agents may be safely continued for the majority of patients undergoing VR surgery.…”
Section: Other Ocular Surgerymentioning
confidence: 99%
“…We would expect a lower risk in surgery for macular hole or epiretinal membrane, compared to delamination for proliferative diabetic retinopathy [2]. Bleeding complications occurred in 17.6% of eyes undergoing surgery for complications of proliferative diabetic retinopathy, compared to 5.8% of eyes undergoing other operations (Fisher's exact test, p = 0.004).…”
mentioning
confidence: 97%
“…[9][10][11][12][13][14] Nonetheless, nearly all of these studies established that such hemorrhagic complications do not cause long-term visual sequelae; most are reported as self-limited vitreous hemorrhages that rarely require return to the operating room. Yet, if surgery was performed for a vascular retinal disease, risks for hemorrhage were greater.…”
mentioning
confidence: 99%